2012
DOI: 10.1029/2010wr010261
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for a priori bias correction in soil moisture data assimilation

Abstract: [1] Data assimilation is increasingly being used to merge remotely sensed land surface variables such as soil moisture, snow, and skin temperature with estimates from land models. Its success, however, depends on unbiased model predictions and unbiased observations. Here a suite of continental-scale, synthetic soil moisture assimilation experiments is used to compare two approaches that address typical biases in soil moisture prior to data assimilation: (1) parameter estimation to calibrate the land model to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 70 publications
3
120
0
Order By: Relevance
“…All evaluation indices were determined for both CLM-Ref and for the ensemble mean of CLM-Ens P . Post et al (2016) showed that parameters estimated for the forest sites WÜ and FR-Fon are well transferable to other FLUXNET sites of corresponding PFTs located more than 600 km from WÜ and FR-Fon: Tharandt in Germany (DE-Tha; e.g., Grünwald and Bernhofer, 2007) and Hainich in Germany (DE-Hai; e.g., Knohl et al, 2003). Because WÜ is the only forested EC tower site in the Rur-catchment and no additional EC towers were available for the validation of the estimated parameters, we assume the parameter estimates provide more reliable NEE data for a large part of the forested area in the Rur catchment.…”
Section: Evaluation Of Parameter Estimates With Eddy Covariance Nee Datamentioning
confidence: 92%
“…All evaluation indices were determined for both CLM-Ref and for the ensemble mean of CLM-Ens P . Post et al (2016) showed that parameters estimated for the forest sites WÜ and FR-Fon are well transferable to other FLUXNET sites of corresponding PFTs located more than 600 km from WÜ and FR-Fon: Tharandt in Germany (DE-Tha; e.g., Grünwald and Bernhofer, 2007) and Hainich in Germany (DE-Hai; e.g., Knohl et al, 2003). Because WÜ is the only forested EC tower site in the Rur-catchment and no additional EC towers were available for the validation of the estimated parameters, we assume the parameter estimates provide more reliable NEE data for a large part of the forested area in the Rur catchment.…”
Section: Evaluation Of Parameter Estimates With Eddy Covariance Nee Datamentioning
confidence: 92%
“…Correlation in time was introduced with an AR(1) model with autoregressive parameter 0.33. These correlations and standard deviations were chosen based on previous data assimilation experiments (Reichle et al, 2010;Kumar et al, 2012;De Lannoy et al, 2012;Han et al, 2015). In this work, only results for precipitation perturbation with σ = 0.5 will be shown, as results for σ = 1.0 were similar.…”
Section: Model Ensemblementioning
confidence: 99%
“…The DA method has been widely applied in hydrology for soil moisture estimation (Han et al, 2012;Kumar et al, 2012;Yan et al, 2015) and flood forecasting (Y. Liu et al, 2012;Abaza et al, 2014).…”
Section: Introductionmentioning
confidence: 99%